The Impact of Corporate Governance Mechanisms on Organisational Efficiency of listed financial firm in Nigeria - Ilugbusi, Bamidele Segun; Olutoye, Adedayo Ebenezer Olutoye; Surulere, Omosuyi Julius; Ige , Folasade Folakemi (African Journal of Stability and Development (AJSD), 2024)
This paper examined the effects of corporate governance on the financial institutions’ efficiency in Nigeria. Using a quantitative ex-post facto research design, the study examines the influence of board attributes (size, independence, gender diversity) and audit committee characteristics (size, independence, financial experience) on organisational efficiency as measured through asset turnover. The results show negative efficiency attributable to board size and positive efficiency for board independence and audit committee size using pooled regression analysis from 2012 to 2023. Surprisingly, financial knowledge in audit committees correlates negatively, suggesting a dangerous degree of over[1]specialisation. The effect of firm size on efficiency is consistently strong and positive. These findings emphasise the undeniable impact of governance on organised effectiveness and provide policy recommendations to support governance best practices in growing economies such as Nigeria. This study makes important contributions to the academic literature and corporate governance policy debate.